Estimasi Sumberdaya Batubara Menggunakan Perbandingan Metode Polygon Dan Cross Section Di Pit I Pt. Atoz Nusantara Mining, Pesisir Selatan, Sumatera Barat - Muhamadinda Debeno Habibie; Heri Prabowo (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. PT. Atoz Nusantara Mining implements an open pit mining system and is currently conducting exploration activities.The current condition of PT. Atoz Nusantara Mining is currently doing land acquisition for what is used as a mining area.To find out in detail the subsurface conditions, the company carries out well logging activities. So hopefully the series of detailed exploration activities can facilitate the company in taking further steps or actions. After the company conducted detailed exploration activities, the company had not yet processed the data to determine the amount of coal resources, volume value, and tonnage in the Pit I area of PT. Atoz Nusantara Mining.With the data above, it will be easier to conduct coal resource calculation activities. To reduce the amount of geological risk, it is necessary to calculate the mature coal resources in analyzing how the subsurface conditions in order to determine the shape, size and dimensions of coal. Resource calculation plays an important role in determining the quantity, quality and ease of commercial exploration of a deposit. Because the results of a good resource calculation can determine the investment to be invested by investors, the determination of production targets, ways of mining that will be carried out even in estimating the time needed by the company in carrying out its mining businessKeywords: exploration, logging activities, coal resources, coal quantity, production target